The Political Dynamic of Dayak Elite on Relocating Capital to Kalimantan Island - Purnama Julia Utami; Sri Musrifah (Budapest International Research and Critics University, 2021)
This study aims to see how pertinent the Dayak elites believe in the transition of relocating their capital to Central Kalimantan. This study uses a historical-dialectical approach to address the Dayak that strengthen their identity. The purpose of this study is to demonstrate the importance of the Dayak in strengthening their identity and reputation. With a newfound identity, Dayak farmers would gain recognition from both the provincial governments and the entire state of Indonesia. From now on, the Dayak would be recognized as a legitimate and valuable population.